Anterior cruciate ligament injury incidence among male and female professional alpine skiers - Viola, R. W.; Steadman, J. R.; Mair, S. D.; Briggs, K. K.; Sterett, W. I. (The American Journal of Sports Medicine, 1999)
A retrospective review of anterior cruciate ligament injuries among professional alpine skiers was performed to compare sex-related differences in injury incidence. We screened 7155 ski patrollers or instructors (4537 men and 2618 women) for knee injuries before each ski season between 1991 and 1997. Screening involved a ski history questionnaire, a knee injury history questionnaire, and a knee physical examination. Any patient with an equivocal Lachman or pivot shift test was evaluated by KT-1000 arthrometry and excluded from the study if the manual maximum side-to-side difference was 3 mm or more. Thus, the study population was limited to subjects with intact anterior cruciate ligaments. Skiers injured during the study were identified through mandatory workers' compensation claims. Each injured skier was reevaluated using an injury questionnaire and physical examination. The men skied an average of 110 days per year (499,070 skier-days) and the women skied an average of 87 days per year (227,766 skier-days). Thirty-one skiing-related anterior cruciate ligament injuries were diagnosed, 21 in men and 10 in women. The incidence of ACL disruption was 4.2 injuries per 100,000 skier-days in men and 4.4 injuries per 100,000 skier-days in women. These data suggest that the incidences of anterior cruciate ligament injuries among male and female professional alpine skiers are similar.